2013
DOI: 10.1097/jnr.0000000000000008
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a Model to Assess the Effects of School Support and Self-Care Behaviors on Life Satisfaction in Adolescents With Type 1 Diabetes in Taiwan

Abstract: School support and self-care behaviors positively influence the life satisfaction of adolescents with type 1 diabetes. Improvements in school support and self-care behaviors are necessary to improve life satisfaction in this vulnerable group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 25 publications
0
9
0
4
Order By: Relevance
“…The psychological consequence to students are less obvious, but equally important: they may purposefully keep blood glucose levels high so as to avoid the embarrassment of such episodes, thus compromising diabetes control and leading to unnecessary risks. Adolescents' perceptions of support from school and the ability to provide DM increased life satisfaction and is essential for adolescents' health …”
Section: Discussionmentioning
confidence: 99%
“…The psychological consequence to students are less obvious, but equally important: they may purposefully keep blood glucose levels high so as to avoid the embarrassment of such episodes, thus compromising diabetes control and leading to unnecessary risks. Adolescents' perceptions of support from school and the ability to provide DM increased life satisfaction and is essential for adolescents' health …”
Section: Discussionmentioning
confidence: 99%
“…In a recent Swedish study, 40% of adolescents had access to one or more designated staff members to support diabetes self‐care but the prevalence of additional staff resources in the classroom because of the presence of a pupil with diabetes was just 3%. While lesser provision of staff support for adolescents with diabetes is likely to be based on an incremental ability to perform diabetes self‐care with increasing age, it contrasts with the results of previous studies which have clearly established that school support directly and significantly affects self‐care behaviours among adolescents . Sixty‐six percent of the variance in life satisfaction in one report was attributable to school support.…”
Section: Discussionmentioning
confidence: 57%
“…In addition, we did not quantify the number of non‐respondents. There were no refusals to complete the questionnaire in a previous Italian study , whereas the response rate in a study solely including adolescents was high at 96% . Finally, as our study methodology was an anonymous survey, some interesting observations were identified during data analysis that we were unable to explore further.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Students spend the majority of their time at school, this gives the school nurse an opportunity to work with students on transition planning. Perceived school support directly influences self-care behavior and life satisfaction for students with type 1 diabetes (Tang, Chen, & Wang, 2013). The school nurse can help the student with type 1 diabetes to acquire the knowledge and skills needed to make responsible decisions by using strategies described above such as a transition planning support group and checklists.…”
Section: Making Choicesmentioning
confidence: 99%